Enhanced perchloroethene dechlorination by humic acids via increasing the dehalogenase activity of Dehalococcoides strains. Issue 4 (28th March 2022) - Wan, Jixing; Chen, Kezhen; Chen, Jingwen; Qin, Zhihui; Adrian, Lorenz; Shen, Chaofeng
Abstract: Perchloroethene (PCE) is a widely used chlorinated solvent. PCE is toxic to humans and has been identified as an environmental contaminant at thousands of sites worldwide. Several Dehalococcoides mccartyi strains can transform PCE to ethene, and thus contribute to bioremediation of contaminated sites. Humic acids (HA) are ubiquitous redox-active compounds of natural aquatic and soil systems and have been intensively studied because of their effect in electron transfer. In this study, we observed the dechlorination of PCE was accelerated by HA in mixed cultures containing Dehalococcoides strains. Anthraquinone-2, 6-disulfonic acid (AQDS), a humic acid analogue, inhibited PCE dechlorination in our cultures and thus induced an opposite effect on PCE dehalogenation than HA. We observed the same effect on PCE dechlorination with the pure culture of Dehalococcoides mccartyi strain CBDB1. Not only in mixed cultures but also in pure cultures, growth of Dehalococcoides was not influenced by HA but inhibited by AQDS. Enzymatic activity tests confirmed the dehalogenating activity of strain CBDB1 was increased by HA, especially when using hydrogen as electron donor. We conclude that HA enhanced PCE dechlorination by increasing the reaction speed between hydrogen and the dehalogenase enzyme rather than acting as electron shuttle through its quinone moieties. Abstract : Humic acids enhanced perchloroethene dechlorination by increasing the reaction speed between hydrogen and dehalogenase other than acting as electron shuttle by quinone moieties.